Closing the representation gap in micro and small enterprises - Edward Webster; Christine Bischoff; Edlira Xhafa; Juçara Portilho Lins; Doreen Delreece Deane; Dan Hawkins; Sharit Bhowmik; Nitin More; Naoko Otani; Sunghee Park; Eustace Imoyera James; Melisa Serrano; et al. (International Labour Organization (ILO), 2008)
The process of increasing informalisation of the labour market is creating a gap between trade unions and a growing number of workers who have no forms of collective representation at their places of work. This has been labelled the Representational Gap. In part this gap is the result of a trend towards the decentralization of production and the accompanying outsourcing of workers to a third party. In other cases it has arisen from the trend towards casualisation, part-time and temporary employment relationships. It is sometimes a result of retrenchment of workers in the face of international competition and the drive to cut labour costs. The result of these processes is a growing number of workers engaging in survival type activities in micro and small enterprises (MSEs). In particular workers in these workplaces have no form of collective representation. This project was initiated by the International Labour Organisation and is designed to identify obstacles and opportunities for closing this representational gap.
Keywords: 330